2021
DOI: 10.52547/archhygsci.10.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fear of Falling, Mental Wellbeing, and Depression in the Elderly With Cardiovascular Disease: A Predictive Study

Abstract: Background & Aims of the Study: This study aimed to determine the relationship between fear of falling, mental wellbeing, and depression in the elderly with cardiovascular disease. Materials and Methods:This descriptive-analytical study was performed on 283 elderly selected per the inclusion and exclusion criteria. The required data were collected using the Center of Epidemiological Studies-Depression Scale (CES-D), the Falls Efficacy Scale International (FES-I), and the World Health Organization-Five Well-Bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The incidence rate of depression in women is about twice that in men, and it is related to functional disability, medical conditions of comorbidity and social deprivation. [ 6 ] The extension of life expectancy leads to the aging of the population. For the elderly, depression is a major public mental health problem.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of depression in women is about twice that in men, and it is related to functional disability, medical conditions of comorbidity and social deprivation. [ 6 ] The extension of life expectancy leads to the aging of the population. For the elderly, depression is a major public mental health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence demonstrated that inactive adult women over 60 years of age are at greater risk for death, fractures, and recurrent falls than active peers of the same age [ 17 ]. The experience of cognitive and motor impairment is more prevalent among older women [ 18 ].…”
Section: Introductionmentioning
confidence: 99%